2008
DOI: 10.5194/bg-5-731-2008
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturized biosignature analysis reveals implications for the formation of cold seep carbonates at Hydrate Ridge (off Oregon, USA)

Abstract: Abstract. Methane-related carbonates from Hydrate Ridge typically show several macroscopically distinguishable mineral phases, namely whitish aragonite, lucent aragonite, and gray micrite. The relationship of these phases to particular microorganisms or biogeochemical processes is as yet unclear. We used a miniaturized biomarker technique on mg samples, combined with factor analysis and subsequent electron microprobe analysis, to study lipid biomarkers and chemical compositions of the individual phases. This a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
32
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 25 publications
(36 reference statements)
2
32
2
Order By: Relevance
“…15) as the dominant carbon source and agree with sulphate-dependent anaerobic oxidation of methane (AOM: CH 4  + SO 4 2−  → HCO 3 −  + HS −  + H 2 O; e.g., ref. 17) – the biogeochemical key process inducing carbonate precipitation at methane seeps (e.g., refs 1, 2, 3, 4). Inside the build-up, upward flow of gaseous methane was facilitated by the porous carbonate framework (permeability ~1.088 * 10 −9  m 2 ; porosity between 5–16 vol.%; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…15) as the dominant carbon source and agree with sulphate-dependent anaerobic oxidation of methane (AOM: CH 4  + SO 4 2−  → HCO 3 −  + HS −  + H 2 O; e.g., ref. 17) – the biogeochemical key process inducing carbonate precipitation at methane seeps (e.g., refs 1, 2, 3, 4). Inside the build-up, upward flow of gaseous methane was facilitated by the porous carbonate framework (permeability ~1.088 * 10 −9  m 2 ; porosity between 5–16 vol.%; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Carbonate build-ups develop at areas of seafloor methane venting where microbially mediated sulphate-dependent anaerobic oxidation of methane produces alkalinity, thus facilitating precipitation of seep-carbonates1234. Seep-carbonates recently gained attention as geological archives, recording past methane release events56 and comprising significant sinks in the carbon cycle78.…”
mentioning
confidence: 99%
“…For example, ANME-1 groups occur at sites of lower methane concentrations (Nauhaus et al, 2005) and greater depths within the sediment than ANME-2, which are often reported to be dominant near the sediment-water interface at high methane flux sites Knittel et al, 2005;Niemann et al, 2005). Biomarkers enclosed in seep carbonates archive such differences (Leefmann et al, 2008;Stadnitskaia et al, 2008). Accordingly, the formation of calcitic nodules such as GeoB 8212-2a was taking place deeper within the sediment and at moderate methane fluxes based on the predominance of diagnostic biomarkers of ANME-1 archaea.…”
Section: Constraints On the Environments Of Carbonate Formation At Thmentioning
confidence: 99%
“…Until now, however, mostly bulk samples have been analysed for biomarkers, whereas only a few studies on modern seep deposits have so far attempted to retrieve information preserved in individual seep carbonate horizons and/or mineral phases (Aloisi et al. 2002; Leefmann et al. 2008; Stadnitskaia et al.…”
mentioning
confidence: 99%
“…2010). On a mm‐scale, a highly selective distribution of lipid biomarkers was found within modern seep carbonate phases from Hydrate Ridge (off Oregon, USA; Leefmann et al. 2008).…”
mentioning
confidence: 99%